Applying lean thinking to improve the production process of a traditional medium-size British manufacturing company. (1st January 2013) - Sigari, Salman; Clark, Robin
A well-organised implementation of lean manufacturing strategy will lead to excellent operations system and continuous improvement through the removal of non-value-added activities. This case study uses value-stream-mapping to investigate non-value-added activities, simply show how lean manufacturing implementation can intelligibility result a framework of improvement. The implementation and improvements will be depicted in the area of lead time, cycle time and quality by applying lean concepts like circle-shape on production line, 5S and Kaizen team on the shop floor of a British medium-size company.